2011
DOI: 10.1007/s10875-011-9547-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interleukin 28B rs12979860 C/T Polymorphism on the Histological Outcome of Chronic Hepatitis C: Relationship with Gender and Viral Genotype

Abstract: IL-28B rs12979860 C/T polymorphism is associated with a greater likelihood of HCV persistence, particularly in HCV genotypes 1 and 4. The T allele affects the severity of liver fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
53
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 28 publications
9
53
0
1
Order By: Relevance
“…Similarly, (Asselah et al, 2012) were not able to find any significant relationship between IL28B rs12979860 polymorphism and fibrosis stage or disease severity, though they reported a significant correlation between IL28B rs12979860 polymorphism and treatment. However, some recent studies showed that the IL-28B rs12979860 T/T genotype is an independent predictor of a higher fibrosis staging score compared to the CC or CT genotypes (Agundez et al, 2010;Falleti et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, (Asselah et al, 2012) were not able to find any significant relationship between IL28B rs12979860 polymorphism and fibrosis stage or disease severity, though they reported a significant correlation between IL28B rs12979860 polymorphism and treatment. However, some recent studies showed that the IL-28B rs12979860 T/T genotype is an independent predictor of a higher fibrosis staging score compared to the CC or CT genotypes (Agundez et al, 2010;Falleti et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…We excluded patients who had other chronic liver diseases, positive hepatitis B surface antigen (HBsAg) and human immunodeficiency virus (HIV). The liver biopsies taken percutaneously were evaluated using the Ishak scoring system (22), which categorizes fibrosis with a score of 0-2 as mild, 3-4 as moderate and 5-6 as severe (23). Subjects in the healthy control group had a mean age of 52.5±11.5 years (age range 18-70) and none had any hepatic disease (i.e., infection, long term drug use, autoimmune-hepatitis or alcohol consumption) or endocrine disease and the results of their liver function tests and liver ultrasonography were normal.…”
Section: Patients and Healthy Subjectsmentioning
confidence: 99%
“…After our selection, 7 casecontrol studies including 1152 HCC and/or LC cases and 1326 controls fulfilled the inclusion criteria (Barreiro et al, 2011;Fabris et al, 2011;Falleti et al, 2011;Agundez et al, 2012;El-Awady et al, 2012;Eurich et al, 2012;Ren et al, 2012). The quality of the studies was considered acceptable for our meta-analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%